PENGARUH KUALITAS PELAYANAN TERHADAP CITRA PERUSAHAAN (STUDI KASUS DI POLITEKNIK LP3I JAKARTA KAMPUS CIBINONG) - Yunita Indriany (POLITEKNIK LP3I JAKARTA, 2019)
Based on observations in the field, it can be seen that at the Polytechnic LP3I Jakarta Cibinong Campus service is generally seen as good enough, but there are some services that are still considered not optimal. Based on this, the writer is interested in conducting research to find out how much influence the quality of service on corporate image (Polytechnic LP3I Jakarta Cibinong Campus). The type of research chosen is a type of quantitative research. Quantitative research was chosen because researchers wanted to measure the effect of service quality on image at the Polytechnic LP3I Jakarta Cibinong Campus using a scale and size that had been previously designed. This measurement is based on the respondent's answer to a questionnaire containing various questions and statements with variations of answers that have been provided by the author. This research is explanative, namely a study that explains the interplay between independent variables (Service Quality) and dependent variables (Image Company) through testing hypotheses. In this case the researcher examines whether there is an influence between the quality of service to the company image by testing several theories used. From the results of the analysis obtained the value of service quality has a significant positive effect on the image shown by the r value of 0.587 which means the relationship between the two is strong. While the coefficient of determination (R2) is equal to 0.344, which means that service quality can increase the company's image variable by 34.4%, while the remaining 65.6% is explained by other variables. Keywords: Service, Quality, Image